Hyers-ulam stability of a perturbed generalised lienard equation (2019)
In this paper, we consider the Hyers-Ulam stability of a perturbed generalized Lienard equation, using a nonlinear extension of Gronwall-Bellman integral inequality called the Bihari integral inequality.